Digitarization of Guidance and Counselling Programme in Tertiary Institutions in Nigeria - Ohunene, Lawal Adijat; M.M, Okolo; Johnson, Adegboyega Gbenga (Research Parks Publishing LLC, 2025)
An investigation was conducted to study the impact of digitizing guidance and counselling in tertiary institutions in Nigeria. The research aimed to examine the use of digital technology in the delivery of guidance and counselling services. The study employed secondary data. The secondary data were collected via online publication and print resources. Findings from the study revealed that digitizing guidance and counselling in tertiary institutions in Nigeria can lead to improvement in accessibility, improvement in quality of counselling service delivery, reduction in cost of service delivery and effective data analysis. Based on this, the management of tertiary institutions in Nigeria should support full digitization of guidance and counselling services in tertiary institutions in Nigeria by providing all the human and materials resources to the units or departments. Private institutions and international organization should support the guidance and counselling units by providing the units with digital facilities and technical support.